COFLEX: a novel set point optimiser and feedforward–feedback control scheme for large, flexible wind turbines - G. Lazzerini; J. Deleuran Grunnet; T. Gybel Hovgaard; F. Caponetti; V. Datta Madireddi; D. De Tavernier; S. P. Mulders (Wind Energy Science)
Large-scale wind turbines offer higher power output but present design challenges as increased blade flexibility affects aerodynamic performance and loading under varying conditions. Although flexible structures are considered in terms of (periodic) load control and aerodynamic stability, the impact of flexibility on the aerodynamic response of the blades is currently not fully addressed in conventional control strategies. The current state-of-the-art control strategy is the tip-speed ratio tracking scheme, which aims to maximise power production in the partial-load region by maintaining a constant ratio between blade velocity and wind speed. However, this approach fails under large deformations, where the deflection and structural twist of the blade impact aerodynamic performance. This work aims to redefine the state-of-the-art wind turbine control with the COntrol scheme for FLEXible wind turbines (COFLEX): a novel feedforward–feedback control scheme that leverages optimal operational set points computed by COFLEXOpt, which is a set point optimiser considering the effects of blade deformations on aerodynamic performance and turbine loading. The proposed combined strategy consists of two key modules. The first module, COFLEXOpt, is an optimisation framework that provides controller set points while allowing constraints to be imposed on various operational, structural, and load properties, such as blade deflection and other structural loads. Set points obtained using COFLEXOpt are agnostic to operating regions, meaning that the operating region boundaries are optimised rather than prescribed. The second module is a feedforward–feedback controller and uses the set point mappings generated with COFLEXOpt, scheduled on wind speed estimates, to evaluate feedforward inputs and feedback to correct modelling inaccuracies and ensure closed-loop stability. A set point smoothing technique enables smooth transitions from partial- to full-load operations. The IEA 15 MW turbine is used as an exemplary case to show the effectiveness of COFLEX in maximising rotor aerodynamic efficiency while imposing blade out-of-plane tip displacement constraints. An analysis of the steady-state optimisation results shows that accounting for blade flexibility leads to variable optimal tip-speed ratio operating points in the partial-load region, and the collective pitch angle can be used to counteract blade torsion, maximising power coefficient while complying with imposed constraints. The established controller, tailored to track these optimised set points and operating points, was evaluated through time-marching mid-fidelity HAWC2 simulations across the entire operational range of the IEA 15 MW reference wind turbine (RWT). These simulations, performed under uniform and turbulent wind inflows, demonstrate excellent agreement between optimised steady states and median values obtained from HAWC2 simulations. Furthermore, the generator power shows an increase of up to 5 % in the partial-load region compared to the reference scheme while maintaining blade deflection at a similar level.